Threat Assumptions & Risk Assessment for Design Prioritization - Raj, Dhenesh (International Journal of Control and Automation, 2018)
The purpose of Risk Management is to create preventative and control systems to deal with the dangers that come with certain actions and assets. Many organizations’ attempts at risk management are carried out in isolated enclaves that are too focused on individual functions. Created a TARA technique that summarizes the vast number of potential information security threats into a digest of just the most probable exposures. Using this strategy, CP Kukreja Architects is able to identify potential adversaries whose goals are within reach but might nonetheless result in unacceptable financial damage.